2022
DOI: 10.3389/fcvm.2022.1071119
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous left atrial appendage closure using the LAmbre device in patients with atrial fibrillation and left atrial appendage thrombus

Abstract: BackgroundLeft atrial appendage closure (LAAC) is considered a valid alternative for the prevention of thromboembolic stroke in patients with persistent left atrial appendage thrombus (LAAT) despite adequate anticoagulation. However, the data on LAAC using the LAmbre device for patients with LAAT is limited. This study was performed to explore efficacy and safety as well as to share the experience of the modified LAAC procedure with the LAmbre device.Materials and methodsA total of 7 patients with persistent L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The most frequently found arrhythmia was persistent AF (18). In our series, the average CHADS-VASC2 score (the most used in the assessment of embolic risk in this population) was 1.4, suggesting that the real risk could be underestimated using this score alone (29)(30)(31), in other series the average was 3 (18). We believe that the evaluation of left atrial size, presence of spontaneous contrast, LAA mechanic dysfunction, evaluated by low velocity in the ostium, morphologymultilobed LAA or cauliflower were associated with a higher incidence of TE events -(32 -35) could contribute to personalize the embolic risk in addition to the CHADS-VASc2 Score.…”
Section: Discussionmentioning
confidence: 65%
“…The most frequently found arrhythmia was persistent AF (18). In our series, the average CHADS-VASC2 score (the most used in the assessment of embolic risk in this population) was 1.4, suggesting that the real risk could be underestimated using this score alone (29)(30)(31), in other series the average was 3 (18). We believe that the evaluation of left atrial size, presence of spontaneous contrast, LAA mechanic dysfunction, evaluated by low velocity in the ostium, morphologymultilobed LAA or cauliflower were associated with a higher incidence of TE events -(32 -35) could contribute to personalize the embolic risk in addition to the CHADS-VASc2 Score.…”
Section: Discussionmentioning
confidence: 65%
“…Turned the Swartz sheath clockwise to facilitate the advancement of the guidewire into the left superior pulmonary vein. Then, replaced the Swartz sheath with a delivery sheath and then delivered the pigtail catheter in the left superior pulmonary vein and dropped the pigtail catheter to the LAA ostium by slowly pulling the sheath and catheter back [ 13 ] Marroquin 2022 Watchman = 1 Watchman FLX = 4 ACP = 3 Amulet Amplatzer = 41 Lambre = 4 N/A N/A 18 53 TEE Standard deployment techniques and no-touch technique (involves avoiding guidewire or catheter manipulation within the LAA by loading the closure device with the delivery sheath in the left superior pulmonary vein) [ 19 ] Beneduce 2019 Watchman FLX = 1 N/A N/A 1 1 3D TEE and fluoroscopy No-touch technique. After transseptal puncture, the delivery sheath was pulled back from the left upper pulmonary vein over a stiff guidewire.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness and safety of LAAC in patients with LAAT have not been validated. However, recent studies have revealed that LAAC can effectively prevent stroke events in patients with LAAT, with minimal procedural complications [ 12 , 13 ]. These findings suggest that LAAT may not be an absolute contraindication for LAAC.…”
Section: Introductionmentioning
confidence: 99%
“…This device incorporates a delivery sheath that does not extend to the distal LAA, thereby reducing the likelihood of embolism. 11,12 In our setting, indication for LAA closure was on DOAC-recurrent stroke for patient number-1, whereas was an ultima ratio treatment option for the other patients. Our dates are consistent with an acute feasibility and safety of this procedure, without affecting the efficacy over the mid-term.…”
Section: Discussionmentioning
confidence: 99%
“…A novel device the LAmbre as a two‐part‐device could potentially render it an optimal choice for LAAC in patients with thrombosis. This device incorporates a delivery sheath that does not extend to the distal LAA, thereby reducing the likelihood of embolism 11,12 …”
Section: Discussionmentioning
confidence: 99%